Fishers of Fish and Fishers of Men: Fishing Imagery in the Hebrew Bible and the Ancient Near East - Yoder, Tyler R. (Explorations in Ancient Near Eastern Civilizations, 2016)
The metaphor is a hallmark of Classical Hebrew poetry. Some metaphors, such as "Yhwh is king" or "Yhwh is warrior," play a foundational role. The same does not hold for metaphors from the fishing industry. Because they had access to only two major freshwater sources, archaeological research demonstrates that this industry did not play a major socioeconomic role in ancient Israel. Fishing has nevertheless made a substantial contribution to prophetic and wisdom literature. All metaphors manifest reality, but given the physical circumstances of a largely agrarian, nonmarine society, what does the sustained presentation of fishing metaphors in the Hebrew Bible communicate?Examining the use of fishing images in the Hebrew Bible is a formidable task that demands an open mind and a capacity to mine the gamut of contemporaneous evidence. In Fishers of Fish and Fishers of Men, Tyler Yoder presents the first literary study devoted to the fishing images used in the Hebrew Scriptures as well as in the Mesopotamian textual records. This calls for a penetrating look into cultural contact with Israel's neighbors to the east (Mesopotamia) and southwest (Egypt). Though nearly all fishing metaphors in the Hebrew Bible carry overt royal or divine connotations that mirror uses well-attested in Mesopotamian literature, this comparative analysis remains a largely untapped area of research. In this study of the diverse literary qualities of fishing images, Yoder offers a holistic understanding of how one integral component of ancient Near Eastern society affected the whole, bringing together the assemblage of disparate materials related to this field of study to enable scholars to integrate these data into related research and move the conversation forward